2003
DOI: 10.1089/154099903770948159
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Arm Swelling after Breast Cancer Surgery

Abstract: Our study highlights two important areas of future research that could reduce the incidence of lymphedema. There is a need to better understand the role that treatment for high blood pressure may play in protecting women from arm edema. Second, the potential effect of weight as a modifiable lymphedema risk factor needs to be studied in more detail in light of the conflicting results of different studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
2
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 23 publications
8
70
2
4
Order By: Relevance
“…14,15 Studies have variously reported evaluation methods including selfreport of symptoms (e.g. heaviness, aching, swelling, loss of function), 16,17 objective measurement (using an array of measurement tools and protocols) [18][19][20] and a combination of the self-re-port and objective measures. [21][22][23][24] The evaluation method-ology is likely to affect incidence findings as recent studies using multiple methods have indicated greater subjective reporting of symptoms compared with objective measurement classification of BCRL.…”
Section: Breast Cancer-related Lymphoedemamentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Studies have variously reported evaluation methods including selfreport of symptoms (e.g. heaviness, aching, swelling, loss of function), 16,17 objective measurement (using an array of measurement tools and protocols) [18][19][20] and a combination of the self-re-port and objective measures. [21][22][23][24] The evaluation method-ology is likely to affect incidence findings as recent studies using multiple methods have indicated greater subjective reporting of symptoms compared with objective measurement classification of BCRL.…”
Section: Breast Cancer-related Lymphoedemamentioning
confidence: 99%
“…Studies have shown a significant association 16 or trend towards association 26 between younger age and subjective reporting of upper limb symptoms. A study using objective arm circumferential measures found the incidence of BCRL in older patients (>55 years old) was significantly higher than younger patients.…”
Section: Agementioning
confidence: 99%
“…When the risk factors were assessed in patients with lymphedema development, no statistically significant difference was found between the cases aged over 45 and under 45 in terms of lymphedema development. Geller et al 21 reported a significant increase in lymphedema development risk in women aged under 45. In many studies where age is assessed in the literature, similar to the results we obtained, this factor did not show a significant effect on lymphedema development.…”
Section: Resultsmentioning
confidence: 98%
“…In many studies where age is assessed in the literature, similar to the results we obtained, this factor did not show a significant effect on lymphedema development. 5,18,20,21,22 When BMI was assessed as a risk factor, it was seen that there was no statistically significant difference between the BMI values of >25 or ≤25 on lymphedema development. In the studies, lymphedema development risk shows a 2-fold increase in cases where BMI is over 30.…”
Section: Resultsmentioning
confidence: 98%
“…Lymphedema is a chronic condition involving accumulation of protein-rich fluid that impacts physical, functional, and psychosocial health and well-being (Beaulac, McNair, Scott, LaMorte, & Kavanah, 2002;Geller, Vacek, O'Brien, & Secker-Walker, 2003;Hull, 1998;Radina & Armer, 2004;Voogd et al, 2003). (Figure 1).…”
Section: Defining Breast Cancer-related Lymphedemamentioning
confidence: 99%